Real time database system data security collection scheme - Zhenyang SHANG; Ruixian YANG (Dianxin kexue)
With application status of the China Petroleum Refining and Chemicals run system MES（manufacturing execution system）in subordinate enterprises as well as the data acquisition interface program in real-time database module, the security risks such as virus, attacks and illegal invasions in production unit automatic control system （DCS, PLC）because of the “two-network integration”were analyzed. Finally, referring to some of the existing domestic industrial insulation products, a complete, viable and secure solution, which has a high reference value for the implementation of petrochemical enterprises MES system real-time database module was proposed.